Synthesis of Al-Al2O3 nanostructures by laser ablation - Afanasyev, D.A.; Ibrayev, N.Kh.; Kasymov, M.E. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The results of synthesis of aluminum nanoparticles (NPs) by laser ablation are presented. Water, ethanol, chlorobenzene were used for the synthesis of NPs as solvents. Measurements of sizes and shapes of NPs are carried out. Particle’s sizes was determined using the dynamic light scattering method. Sizes of nanoparticles depends on the boiling point of solvents. Electron microscopic images show that the formation of spherical nanoparticles. Absorption spectra of solutions of aluminum NPs and aluminum oxide (Al2O3) NPs are measured. A computer simulation of extinction spectra of aluminum NPs and Al2O3 NPs in an aqueous solution was also carried out. Extinction spectra of Al and Al2O3 nanoparticles of different sizes in the water were calculated by using Mie theory. The comparison of results of measurements and the simulation showed a significant difference. Luminescence spectra of aqueous solutions of aluminum NPs and aluminum oxide NPs were measured with the ultraviolet excitation. Results of measuring of the luminescence spectrum of the water of aluminum NPs indicate the presence of Al2O3.
Лазерлік абляция əдісімен Al-Al2O3 наноқұрылымдардың синтезі
Синтез наноструктур Al-Al2O3 методом лазерной абляции
Keywords: Al nanoparticles; Al2O3 nanoparticles; Al-Al2O3 nanoparticles; absorption spectrum; luminescence